An Interesting Case of Barbiturate Automatism and Review of Literature - Sankalp Gokhale; Ciro Ramos-Estebanez (Case Reports in Neurological Medicine)
A 48 year old man with a diagnosis of HIV infection since 1993, on highly active anti-retro viral therapy (HAART) with stable CD4 count and undetectable viral load for years and seizure disorder presented with recurrent drowsiness. His seizures were well controlled on phenobarbitone for years. Repeated laboratory evaluation demonstrated toxic levels of phenobarbitone in his blood. A thorough clinical, psychiatric, laboratory and imaging evaluation did not reveal any obvious etiology for the recurrent barbiturate intoxication in this man. Our findings suggest the possible diagnosis of barbiturate drug automatism in this patient. Though drug automatism is a controversial entity, it merits continued attention. There are recent reports of similar phenomenon with newer sedative agents such as Zolpidem. It is important to be aware of this phenomenon as a possible explanation for recurrent intoxication with barbiturates without a clear etiology for drug overdose.